2004
DOI: 10.1111/j.1467-9620.2004.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intelligences: From the Ivory Tower to the Dusty Classroom— but Why?

Abstract: This article draws on research conducted over a 10-year period in an attempt to answer three central questions about the widespread adoption of Gardner's theory of multiple intelligences (MI): Why do educators adopt MI? Once MI is adopted, does anything really change in practice? When educators claim MI is working, what is happening in practice ?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 4 publications
1
15
0
3
Order By: Relevance
“…However, detractors of the theory believe that it lacks any empirical evidence that would make it suitable for classroom application (Waterhouse, 2006). Some researchers also warn against using the theory because it may be misunderstood (Hoerr, 1996; Kornhaber, Fierros, & Veenema, 2004). For example, Hoerr (1996) argued that teachers tend to expose students to all kinds of intelligences in every lesson, while Kornhaber et al (2004) suggested that teachers tend to utilize only low-level and superficial activities when they use MI theory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, detractors of the theory believe that it lacks any empirical evidence that would make it suitable for classroom application (Waterhouse, 2006). Some researchers also warn against using the theory because it may be misunderstood (Hoerr, 1996; Kornhaber, Fierros, & Veenema, 2004). For example, Hoerr (1996) argued that teachers tend to expose students to all kinds of intelligences in every lesson, while Kornhaber et al (2004) suggested that teachers tend to utilize only low-level and superficial activities when they use MI theory.…”
mentioning
confidence: 99%
“…Despite the existence of a large body of research that has addressed the employability of MI in classrooms (Anderson, 2007; Armstrong, 2009; Huebner, 2010; Kornhaber et al, 2004; Lash, 2004; Loori, 2005; Richards & Rodgers, 2001; Snider, 2001), few studies have been conducted on foreign language acquisition using MIs, especially in the preschool setting (Campbell et al, 2004; Folse, 2004).…”
mentioning
confidence: 99%
“…Gardner (2006) w odpowiedzi przywołuje kilkuletnie badania prowadzone w 41 amerykańskich szkołach przez zespół z Uniwersytetu Harvarda. Badania te, prowadzone zarówno w strategii ilościowej, jak i jakościowej, wskazują na pozytywne rezultaty stosowanych programów wraz z ocenianiem zgodnym z indywidualnym profilem inteligencji ("fair-intelligence" assessment) (Kornhaber, Fierros, Veenema, 2004). Czy wobec tak bogatego materiału badawczego jedynie "nowatorstwo i atrakcyjność programów" mogłoby być przyczyną pozytywnych efektów zastosowania teorii inteligencji wielorakich?…”
Section: Wyższość Psychometrii?unclassified
“…Increasingly, teachers are recognising that students learn and excel in a wide variety of ways, and if strengths in their intelligences can be identified, the processes of teaching-learning will be enhanced. A class which offers a variety of learning opportunities increases its students' chances of success [51,54].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%